The Philosophical Structure of Historical Explanation - Roth, Paul (Northwestern University Press, 2019)
Roth develops an argument that resolves disputes persisting since the 19th century about the scientific status of history. He does this by showing why historical explanations must take the form of a narrative, making their logic explicit, and revealing how the rational evaluation of narrative explanation becomes possible. The book also develops a nonrealist/irrealist metaphysics and epistemology of history-arguing that there exists not one fixed past but many. It includes a novel reading of Kuhn's The Structure of Scientific Revolutions, displaying how it offers a narrative explanation of theory change in science, and situates narrative explanations within a naturalistic framework. The first 4 chapters defuse methodological and metaphysical objections to narrative explanations. The final 3 chapters explore how narrative explanations relate to other sciences. It will be of interest to researchers in historiography, epistemology, and philosophies of history, science, and social science.